Urban Tourist Complexes as Multi-Product Companies: Market Segmentation and Product Differentiation in Amsterdam - Jo\~ao Rom\~ao; Bart Neuts; Peter Nijkamp; Eveline van Leeuwen (European Regional Science Association (ERSA), 2012)
The tourism sector is evolving into an advanced industrial sector. Modern tourism presupposes an attractive portfolio of tourist services for a varied set of visitors. Meanwhile, tourism destinations have turned into multifaceted tourist complexes comprising a broad package of amenities that satisfy the needs of a heterogeneous group of clients. Such tourist complexes may be regarded as export-oriented multi-product companies, characterized by spatial and functional market segmentation and by monopolistic competition reflected in product differentiation. This paper argues that tourism becomes a diversified globally-oriented export industry which has to serve a multiplicity of clients. The previous observations prompt intriguing questions on the heterogeneity, motivations, satisfaction and loyalty of tourists. The present work aims to offer a causal path model that depicts the multidimensional attraction force of a particular international tourism centre, viz. Amsterdam, from the perspective of a varied supply of tourism services. After presenting the design of a conceptual model, the empirical implications of offering a multi-product package to a heterogeneous group of visitors are modelled using a structural equations model (SEM). The primary goal of this study was to assess the impact of several factors on the loyalty (measured by the possibility of a return visit or a recommendation to visit to others) to the destination of Amsterdam. The main factors analysed in our study were personal characteristics of tourists, their motivations to visit the city and the satisfaction with the destination. The various findings are interpreted, while policy implications are also outlined. One of the most important findings was that the relationships identified between the levels of satisfaction of tourists and the loyalty to Amsterdam as a tourist destination shows that tourists who achieve higher levels of satisfaction with intangible aspects of the city tend to be more loyal than those who achieve more satisfaction with the tangible aspects of Amsterdam. Another significantly positive effect on loyalty was found for tourists in the lower income categories, tourists with a higher level of education and non-European tourists.
Keywords: 330